2003
DOI: 10.2525/ecb1963.41.121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light Quality on Growth of Crop Plants under Artificial Lighting

Abstract: Major light factors affecting plant growth are light quality, light intensity, photoperiod, and the day/night cycle. These parameters can be controlled under greenhouse conditions using artificial light sources. Moreover, application of light pulses and shortterm changes of the spectral composition are effective ways to stimulate plants and to induce desired morphological developments.Controlling spectral qualities of the irradiation applied enables faster growth or higher yield at a given radiation energy, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 69 publications
1
47
0
2
Order By: Relevance
“…Under the canopy, the proportions of blue light and red light are decreased; those of green and farred light are slightly increased (Smith, 1982;Kasajima et al, 2006). When plants sense the low red:far-red ratio (R:FR) by dense plant canopies, they elongate more rapidly and accelerate development to produce seeds early for survival (Goto, 2003). In the present study, increased green light under the dense canopies might function to regulate the development and culm elongation.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Under the canopy, the proportions of blue light and red light are decreased; those of green and farred light are slightly increased (Smith, 1982;Kasajima et al, 2006). When plants sense the low red:far-red ratio (R:FR) by dense plant canopies, they elongate more rapidly and accelerate development to produce seeds early for survival (Goto, 2003). In the present study, increased green light under the dense canopies might function to regulate the development and culm elongation.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, LEDs have a pronounced peak wavelength in monochromatic green light (Goto, 2003). The spectral range of green light is 500−550 nm (Kasajima et al, 2007), and that of photosynthetic photon fl ux density (PPFD) is 400− 700 nm.…”
mentioning
confidence: 99%
“…1 The importance of light quality in plant growth has been previously reviewed. 41,42 PAR is generally monopolized for research focused on photosynthesis;…”
Section: Importance Of Light Source Spectra Compositionmentioning
confidence: 99%
“…Much research has been carried out on the action spectrum of photosynthesis [24]. However, the effect of different RB-LED ratios on photosynthesis of specific species remains unclear [25] [26]. For instance, studies with red leaf lettuce, showed that the difference of 5% to 10% blue-LED changed total dry weight of the plants significantly.…”
Section: Photosynthetic Light Utilization Of B Alboglabra Grown Undementioning
confidence: 99%